1998
DOI: 10.1073/pnas.95.21.12637
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 400-year-old Yersinia pestis DNA in human dental pulp: An approach to the diagnosis of ancient septicemia

Abstract: Ancient septicemic plague epidemics were reported to have killed millions of people for 2 millenniums. However, confident diagnosis of ancient septicemia solely on the basis of historical clinical observations is not possible. The lack of suitable infected material has prevented direct demonstration of ancient septicemia; thus, the history of most infections such as plague remains hypothetical. The durability of dental pulp, together with its natural sterility, makes it a suitable material on which to base suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
259
5
20

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(304 citation statements)
references
References 31 publications
20
259
5
20
Order By: Relevance
“…In general, this approach has been used for the detection of tuberculosis [1±10], and also for the identi®cation of other pathogens, such as M. leprae [22,23], Plasmodium falciparum [24], Trypanosoma cruzi [25], Yersinia pestis [26] and Escherichia coli [27]. Previous studies had shown that this approach is applicable to ancient Egyptian material, as M. tuberculosis was identi®ed in one of the mummies investigated [5].…”
Section: Discussionmentioning
confidence: 99%
“…In general, this approach has been used for the detection of tuberculosis [1±10], and also for the identi®cation of other pathogens, such as M. leprae [22,23], Plasmodium falciparum [24], Trypanosoma cruzi [25], Yersinia pestis [26] and Escherichia coli [27]. Previous studies had shown that this approach is applicable to ancient Egyptian material, as M. tuberculosis was identi®ed in one of the mummies investigated [5].…”
Section: Discussionmentioning
confidence: 99%
“…Whether these historically described diseases correspond to bubonic plague, whose aetiological agent was identified to be the bacterium now known as Yersinia pestis by Alexandre Yersin in 1894 (Yersin, 1894), has been the subject of controversy (Cohn, 2002;Scott & Duncan, 2001). Recently, DNA specific for Y. pestis was amplified from 16th and 18th century human teeth believed to be from French plague victims (Drancourt et al, 1998) and 14th century French Black Death victims (Raoult et al, 2000). The lead authors of these reports believe that the consideration of any cause for the Black Death other than Y. pestis is now speculative .…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Since the first publication announcing ancient human dental pulp containing Yersinia pestis ancient DNA, 41 scientists have reconstructed its full genome, 42 reconstructed its evolutionary history, 43 and suggested the potential endemicity of the plague in Europe 44, 45 and the Middle East, 46 all of which open new historical questions. Other studies have also broadened the historical narrative in various ways: adding more whole genomes to the pool of Y pestis data, 47 highlighting the variety of potential Y pestis hosts and vectors 48,49 and the role of microclimates in pathogen survival, 50 exploring immunological responses, 51 assessing mortality patterns, 52 and suggesting a potential route and impact of the plague in historical sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%